(untitled) (International Journal of Innovative Computing, 2014)
The objective of this development research is toexplore the application of Bloom’s Taxanomy in the generationof examination question items process. In addition, assessmentof the item’s complexity will also be addressed. This paperprovides the explanation, description and information about theGeneration and Assessment of Examination Question (GAEQ)for the use of the lecturers in higher learning institute. Thecurrent process to generate the examination questions andassess their complexity is done separately and manually. Thecontribution of this paper is the integration of Bloom’sCognitive Domain in both generating and assessing theexamination question. The assessment process will automaticallymeasure the complexity level of the question items. GAEQ willthen compile those items and create a complete finalexamination question set. Hence, it is the aim of the GAEQsystem to initiate and develop a system to assist the lecturers inproducing quality examination questions.